Effects of in-season low-volume high-intensity plyometric training on explosive actions and endurance of young soccer players - Ramirez-Campillo, R.; Meylan, C.; Álvarez, C.; Henriquez-Olguin, C.; Martinez, C.; Cañas-Jamett, R.; Andrade, D. C.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the efficiency of short-term vertical plyometric training program within soccer practice to improve both explosive actions and endurance in young soccer players. Seventy-six players were recruited and assigned either to a training group (TG; n = 38; 13.2 ± 1.8 years) or a control group (CG; n = 38; 13.2 ± 1.8 years) group. All players trained twice per week, but the TG followed a 7-week plyometric program implemented within soccer practice, whereas the CG followed regular practice. Twenty-meter sprint time (20-m), Illinois agility test time, countermovement jump (CMJ) height, 20- (RSI20) and 40- (RSI40) cm drop jump reactive strength index, multiple 5 bounds distance (MB5), maximal kicking test for distance (MKD), and 2.4-km time trial were measured before and after the 7-week period. Plyometric training induced significant (p < 0.05) and small to moderate standardized effect (SE) improvement in the CMJ (4.3%; SE = 0.20), RSI20 (22%; SE = 0.57), RSI40 (16%; SE = 0.37), MB5 (4.1%; SE = 0.28), Illinois agility test time (-3.5%, SE = -0.26), MKD (14%; SE = 0.53), 2.4-km time trial (-1.9%; SE = -0.27) performances but had a trivial and nonsignificant effect on 20-m sprint time (-0.4%; SE = -0.03). No significant improvements were found in the CG. An integrated vertical plyometric program within the regular soccer practice can substitute soccer drills to improve most explosive actions and endurance, but horizontal exercises should also be included to enhance sprinting performance.